Health and Human Wellbeing in China: Do Environmental Issues and Social Change Matter? - Zhao, Wenjuan; Chang, Miao; Yu, Lei; Sohail, Muhammad Tayyab (Frontiers in Psychology, 2022)
How to mitigate greenhouse gas emission and achieve human development remain major sustainability issues, particularly in China. Empirical research on the effects of climate warming and social change on human health and well-being is quite fragmented. This study examines the impact of environmental issues and social changes on health and human well-being using a time series data of China from 1991 to 2020. Findings show that environmental issues have a negative impact on health and human well-being in long run. While the internet is a form of social change that tends to improve health and human well-being in long-run. FDI exerts a positive effect on human health, but it does not improve well-being in the long-run. In contrast, financial development does not improve human health but it has a significant positive impact on well-being in long-run. Our empirical insights have important implications for achieving human well-being through the pursuit of environmental sustainability and social change.